2019
DOI: 10.3390/mi10030163
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Spectral Filter in C-Band Based on Digital Micromirror Device

Abstract: Optical filters have been adopted in many applications such as reconfigurable telecommunication switches, tunable lasers and spectral imaging. However, most of commercialized filters based on a micro-electrical-mechanical system (MEMS) only provide a minimum bandwidth of 25 GHz in telecom so far. In this work, the programmable filter based on a digital micromirror device (DMD) experimentally demonstrated a minimum bandwidth of 12.5 GHz in C-band that matched the grid width of the International Telecommunicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…LCoS device combing with gratings can be further developed as programmable PSP for processing optical spectrum resources [15]. Recently, demonstrations have been reported on generating a reconfigurable PSP [15][16][17][18]. In [15], Gao et al proposed and demonstrated a flexible PSP based on a 4K LCoS with a minimum pixel spacing of 3.74 µm.…”
Section: Of 11mentioning
confidence: 99%
“…LCoS device combing with gratings can be further developed as programmable PSP for processing optical spectrum resources [15]. Recently, demonstrations have been reported on generating a reconfigurable PSP [15][16][17][18]. In [15], Gao et al proposed and demonstrated a flexible PSP based on a 4K LCoS with a minimum pixel spacing of 3.74 µm.…”
Section: Of 11mentioning
confidence: 99%
“…This special issue contains twelve research papers covering MEMS mirrors [1,2,3,4,5,6,7,8,9,10], MEMS variable optical attenuators (VOAs) [11], and tunable spectral filters [12]. These MEMS devices are based on three of the commonly used actuation mechanisms: electrothermal [1], electrostatic [2,3,4,5,6,7,11], and electromagnetic actuation [8,9,10]. MEMS optical scanners involving single mirrors are demonstrated or used in [1,2,3,8,9,10], while all other optical microsystems employ MEMS mirror arrays that are all based on DMDs [4,5,6,7].…”
mentioning
confidence: 99%
“…These MEMS devices are based on three of the commonly used actuation mechanisms: electrothermal [1], electrostatic [2,3,4,5,6,7,11], and electromagnetic actuation [8,9,10]. MEMS optical scanners involving single mirrors are demonstrated or used in [1,2,3,8,9,10], while all other optical microsystems employ MEMS mirror arrays that are all based on DMDs [4,5,6,7]. This special issue also includes one review paper on metalens-based miniaturized optical systems [13].…”
mentioning
confidence: 99%
See 2 more Smart Citations